Diethyldithiocarbamate-copper complex ignites the tumor microenvironment through NKG2D-NKG2DL axis - Dumut, Daciana C.; Hajduch, Marian; Zacharias, Amanda M.; Duan, Qingling; Frydrych, Ivo; Rozankova, Zuzana; Popper, Miroslav; Garic, Dusan; Paun, Radu Alexandru; Centorame, Amanda; Shah, Juhi; Mistrik, Martin; et al. (Frontiers in Immunology, 2025)
Advanced metastatic colorectal cancer (CRC) with deficient DNA mismatch repair (MMR-d), or immune-hot CRCs, show significantly improved clinical outcomes compared to MMR-proficient (MMR-p), or immune-cold CRCs. While the prior represents about 5% of all CRCs, the latter represent 95% and are characterized by low immunogenicity. This study investigates bis-diethyldithiocarbamate (CuET), a novel anticancer compound, and its impact on the colorectal cancer tumor microenvironment (TME). CuET is shown to convert immunologically inactive tumors into hotbeds of antitumor immune responses, marked by increased lymphocyte infiltration, heightened cytotoxicity of natural killer (NK) and T cells, and enhanced non-self recognition by lymphocytes. The potent anticancer cytotoxicity and in vivo safety and efficacy of CuET are established. In summary, CuET transforms the colorectal cancer TME, bolstering NK and T cell cytotoxicity and refining tumor cell recognition through non-classical activation via the NKG2D/NKG2DL axis. This study unveils a novel mechanism of action for CuET: a potent immunomodulator capable of turning cold tumors hot.